Importance of ultrasonography in the diagnosis of massetric abscess - L S Vagish Kumar (Wolters Kluwer Medknow Publications, 2015)
Abscess of massetric region are frequently misdiagnosed as parotid abscess. Ultrasonography, particularly is of immense help to differentiate between these lesions. This case highlights the importance of ultrasonography in this particular context.